SAE Technical Paper Series 2016
DOI: 10.4271/2016-01-1761
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Substructuring for Sources Contributions Analysis in Internal Combustion Engines

Abstract: For vibration and acoustics vehicle development, one of the main challenges is the identification and the analysis of the noise sources, which is required in order to increase the driving comfort and to meet the stringent legislative requirements for the vehicle noise emission. Transfer Path Analysis (TPA) is a fairly well established technique for estimating and ranking individual low-frequency noise or vibration contributions via the different transmission paths. This technique is commonly applied on test me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In common FMBD systems for industrial applications, the contacts between different bodies are often nonlinear. In order to analyze the dynamics of a substructure considering nonlinear connections at interfaces, a numerical transfer path analysis, based on the sub structuring of a multibody system, was proposed [23,24]. The aim of this methodology is to decompose the original system in order to identify vibro-acoustic sources and noise paths of a vibrating subsystem.…”
Section: Sub Structuring Of Multibody System For Numerical Transfer Path Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In common FMBD systems for industrial applications, the contacts between different bodies are often nonlinear. In order to analyze the dynamics of a substructure considering nonlinear connections at interfaces, a numerical transfer path analysis, based on the sub structuring of a multibody system, was proposed [23,24]. The aim of this methodology is to decompose the original system in order to identify vibro-acoustic sources and noise paths of a vibrating subsystem.…”
Section: Sub Structuring Of Multibody System For Numerical Transfer Path Analysismentioning
confidence: 99%
“…The transmissibility based method known as Operational TPA, developed to overcome the disadvantage of having individual measures of each single path from a source to a receiver, was developed by Nomura and Yoshida [19]; further reviews and benchmark studies can be found in [20,21].Recent applications combine the TPA methodology with the novelty of numerical simulations. The Hybrid TPA formulation (HTPA) uses simulated excitation forces as input for TPA analysis, where the vibro-acoustic transfer functions are measured [22], while the Numerical TPA (NTPA) proposed in [23,24] is based on the Dynamic Sub structuring (DS) of flexible multi-body systems.…”
Section: Introductionmentioning
confidence: 99%
“…Most research has been performed in this area with balance shaft application with four-stroke inline three-cylinder units as the subject engine [6][7][8][9][10]. Two-stroke cycle engines for range extenders or hybrid drive train have been researched by Stan and Personnaz [11], Mattarelli et al [12], Borgi et al [13] and Hooper [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…6 Alternatively, the couple can be successfully counteracted by more direct methods via the addition of a contra-rotating balance shaft designed to cancel the action of the couple. This has been considered via the studies by Kim et al, 4 Acri et al, 7 Coltman et al, 8 Suh et al 9 and Heifetz and Marsh. 10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation